Validation of the Chinese Velopharyngeal Insufficiency Effects on Life Outcomes Instrument. (22nd January 2019) - Huang, Hanyao; Chen, Nan; Yin, Heng; Skirko, Jonathan R.; Guo, Chunli; Ha, Pin; Li, Jingtao; Shi, Bing
Abstract : Objectives/Hypothesis: To translate the Velopharyngeal Insufficiency Effects on Life Outcomes (VELO) instrument into Chinese and test its psychometric properties. Study Design: Quality of life instrument translation and validation. Methods: The original English version of the VELO instrument was translated into Mandarin, back‐translated, and adapted among the Chinese population, based on the standardized guidelines for the cross‐culture adaption process. Velopharyngeal insufficiency (VPI) patients were identified by a professional speech and language pathologist. Internal reliability of the VELO instrument was assessed by the Cronbach's α coefficient. Discriminant validity was tested by the Mann‐Whitney U test. Construct validity was assessed by factor analysis. Results: A total of 113 patients with VPI and 72 parents of the patients were enrolled. The mean age of the VPI patients was 14.8 years. Internal reliability was excellent; Cronbach's α coefficients were 0.92 and 0.94 for VPI patients and their parents, respectively. The Chinese VELO discriminated well between the VPI group and the controls, with a mean (standard deviation) score that was significantly lower for the VPI group (74.8 [25.7]) than the control group (98.0 [15.9]) ( P < .001). The total scores and scores in the emotional domain or perception domain showed differences between VPI patients and their parents. Similar to the original study, the factor loading after rotation followed hypothesized domains largely, in spite of items from several domains loaded on the same factor. Conclusions: The translated Chinese version of the VELO instrument demonstrated an acceptable reliability, discriminant validity, and construct validity. These psychometric properties suggested theoretical evidence for the further use of the VELO instrument among Chinese patients with VPI. Level of Evidence: 3b Laryngoscope, 129:E395–E401, 2019